Pengaruh Kepemimpinan Instruksional, Kecerdasan Emosional dan Motivasi Kerja Terhadap Kinerja Guru Smk Negeri Se Kota Palangka Raya - Retty Marinda; Ahmad Suriansyah; Suhaimi Suhaimi (Universitas Negeri Malang, 2020)
Abstract: Teacher performance refers to the tangible results achieved by teachers in carrying out their duties in accordance with established standards. It includes lesson planning, instructional delivery, classroom management, and the evaluation of student learning outcomes. Performance is measured based on the quality and quantity of work within a specific time frame, aimed at achieving educational goals. This study aims to analyze the direct and indirect effects of instructional leadership, emotional intelligence, and work motivation on the performance of public vocational high school (SMK Negeri) teachers in Palangka Raya City. A quantitative approach using path analysis was employed. The study population consisted of 386 teachers, with a sample of 196 selected through proportional random sampling. Data were collected using questionnaires consisting of four instruments: instructional leadership of school principals (28 items), emotional intelligence (24 items), work motivation (20 items), and teacher performance (26 items). The instruments were tested for validity using item analysis with product-moment correlation, and reliability using Cronbach’s alpha. The results show: 1) There is a direct effect of principals’ instructional leadership on teacher performance; emotional intelligence has a direct effect on teacher performance; work motivation directly affects teacher performance; instructional leadership directly influences teacher work motivation; and emotional intelligence directly influences teacher motivation. 2) There is an indirect effect of instructional leadership on teacher performance through work motivation, and emotional intelligence also indirectly affects teacher performance through work motivation. Keywords: Instructional Leadership; Emotional Intelligence; Work Motivation; Teacher Performance. Abstrak: Kinerja guru adalah hasil kerja nyata dalam menjalankan tugas sesuai standar, mencakup perencanaan, pelaksanaan, pengelolaan kelas, serta evaluasi pembelajaran. Kinerja diukur dari kualitas dan kuantitas kerja dalam kurun waktu tertentu untuk mencapai tujuan pendidikan. Penelitian bertujuan untuk menganalisis pengaruh langsung dan tidak langsung kepemimpinan instruksional, kecerdasan emosional dan motivasi kerja terhadap kinerja guru SMK Negeri di Kota Palangka Raya. Penelitian ini menggunakan pendekatan kuantitatif dengan model analisis jalur. Populasi penelitian ini adalah 386 orang guru dengan sampel sebanyak 196 orang yang diambil dengan menggunakan teknik proporsional random sampling. Pengumpulan data menggunakan instrumen angket yang terdiri dari variabel kepemimpinan instruksional kepala sekolah (28 item), instrumen kecerdasan emosional (24 item), instrumen motivasi kerja (20 item) dan instrumen kinerja guru (26 item). Instrumen diuji validitas mengunakan analisi butir dengan korelasi product moment sedangkan reliabilitasnya dengan alpa cronbach. Hasil penelitian menunjukkan bahwa: terdapat pengaruh langsung kepemimpinan instruksional kepala sekolah secara langsung terhadap kinerja guru; kecerdasan emosional secara langsung terhadap kinerja guru; Motivasi kerja secara langsung terhadap kinerja guru; Kepemimpinan instruksional kepala sekolah secara langsung terhadap motivasi kerja guru; kecerdasan emosional terhadap terhadap motivasi guru. 2). Terdapat pengaruh tidak langsung kepemimpinan instruksional kepala sekolah melalui motivasi kerja terhadap kinerja guru kecerdasan emosional melalui motivasi kerja terhadap kinerja kerja guru. Kata kunci: Kepemimpinan Instruksional; Kecerdasan Emosional; Motivasi Kerja; Kinerja Guru